2014
DOI: 10.1186/1471-2369-15-96
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tissue yield for percutaneous native kidney biopsy according to practitioner and ultrasound technique

Abstract: BackgroundAlthough percutaneous renal biopsy remains an essential tool in the diagnosis and treatment of renal diseases, in recent times the traditional procedure of nephrologists has been performed by non-nephrologists rather than nephrologists at many institutions. The present study assessed the safety and adequacy of tissue yield during percutaneous renal biopsy according to practitioners and techniques based on ultrasound.MethodsThis study included 658 native renal biopsies performed from 2005 to 2010 at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 27 publications
3
36
0
Order By: Relevance
“…One retrospective study found no difference in diagnostic yield or complications (hematoma, need for transfusion, gross hematuria, pain, or infection) between ultrasoundmarked, blind PRBs performed by nephrologists (n=271) and real-time/ultrasound-guided PRBs performed by nephrologists (n=170) or radiologists (n=217) (30). It should go without saying that a kidney biopsy should only be done by someone skillful in performing the procedure and when the tissue can be processed and interpreted by those with the skills necessary to do so (14).…”
Section: Biopsy Operatormentioning
confidence: 99%
“…One retrospective study found no difference in diagnostic yield or complications (hematoma, need for transfusion, gross hematuria, pain, or infection) between ultrasoundmarked, blind PRBs performed by nephrologists (n=271) and real-time/ultrasound-guided PRBs performed by nephrologists (n=170) or radiologists (n=217) (30). It should go without saying that a kidney biopsy should only be done by someone skillful in performing the procedure and when the tissue can be processed and interpreted by those with the skills necessary to do so (14).…”
Section: Biopsy Operatormentioning
confidence: 99%
“…Percutaneous renal biopsy was done by nephrologists under ultrasonographic guidance using an automated biopsy gun as previously described [8]. Histopathologic diagnosis on each sample was made comprehensively based on all clinical data and pathologic findings.…”
Section: Case Presentationmentioning
confidence: 99%
“…Ultrasound-guided percutaneous renal biopsy (PRB) is an important technique for making diagnosis and obtaining prognostic information for the treatment of glomerular diseases [1,2]. Although PRB has some complications mainly related to bleeding [2,3], life-threatening complications of PRB occur in only \0.1 % of cases [4][5][6].…”
Section: Introductionmentioning
confidence: 99%